Differentiation between poverty and exclusion for its correct identification in an intermediate urban area - Calle-Espinosa, Cristina (Sociedad y Economía, 2018)
The objective of this article is to reflect on the differences between the concept of poverty and the concept of exclusion, and thus properly identify each of these phenomena in an intermediate urban environment. In order to achieve this goal, a conceptual framework on poverty and exclusion is presented, to give rise to an analysis about an intermediate city in Argentina, which shows a moderate incidence of poverty, but appreciable patterns of exclusion. Subsequently, poverty is measured using fuzzy sets, and exclusion is evaluated using the dimensions proposed by Burchardt, Le Grand y Piachaud (1999). The main conclusion of this article is that in an urban context with relatively low poverty rates, situations of exclusion may occur that do not necessarily correspond to situations of deprivation and vice versa.